Effect on paternal supplementation of palm oil (Tocotrienol Rich Fraction) on male fertility / Nik Nur Syamimi Nik Mat - Nik Mat, Nik Nur Syamimi (2015)
Infertility is defined as a reproductive system disease or problem that gives inability to having pregnancies and half of the cases are related to male infertility. Palm oil, Tocotrienols, a component of vitamin E, showed the strength to improve the functions of male reproductive system. This study was performed to investigate the improvement of male fertility through paternal supplementation of Vitamin E Palm Oil Tocorienol Rich Fraction (TRF) on male rat's model. A fifteen male rats of Albino Wistar were divided into 5 groups (n=3). Control negative group (F) was orally administered with distilled water (0.1 ml), control positive group (0) was orally administered with vitamin E-free com oil (O.1ml) and treatment groups were orally administered with three different concentrations of TRF, at a dose of 30 mg/kg (H), 60 mg/kg (1) and 90 mg/kg (1) respectively. After 7 days of acute treatment, the blood was collected using retro orbital sinus technique for biochemical investigation and hormonal analysis. The rats were sacrificed using cervical dislocation technique. The sperm were collected from cauda epididymis for sperm analysis. TRF supplementation induced improvement in sperm morphology and motility compared to control negative group (F). Other than that, TRF also provide positive effects to the liver and renal function by result on reducing blood glucose and total bilirubin level. Hormonal analysis demonstrated the ability of TRF to enhance LH production, which action to enhance spermatogenesis, thus help in fertility booster. This study suggested that TRF possesses the potential as anti-infertility agent and beneficial to the renal and liver function.